2015
DOI: 10.1186/s13613-015-0100-x
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic chest B-lines anticipate elevated B-type natriuretic peptide level, irrespective of ejection fraction

Abstract: BackgroundEchocardiography and the N-terminal pro-brain-type natriuretic peptide (NT-proBNP) level are important tests for assessing left ventricular function in patients presenting to the emergency department with acute dyspnea. Chest ultrasound is becoming an important tool in diagnosing acute pulmonary edema.AimTo assess the diagnostic accuracy of chest ultrasound examination using echocardiography and a curvilinear probe for detecting B-lines in patients presenting with acute pulmonary edema compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 16 publications
1
14
1
1
Order By: Relevance
“…These studies raise the need for tests that investigate the role of cardiac dysfunction in patients experiencing COPD exacerbations. Our study is consistent with previous studies on the utility of LUS in identifying patients with elevated NP in patients with heart failure, that is LUS B‐lines are specific (~90%) but the sensitivity is variable (30–90%) . In this study of patients with COPD exacerbations, we also found that LUS B‐lines have moderate sensitivity for identifying patients with elevated NP.…”
Section: Two‐way Paired Comparisons Between Acute Exacerbation Of Chrsupporting
confidence: 91%
See 1 more Smart Citation
“…These studies raise the need for tests that investigate the role of cardiac dysfunction in patients experiencing COPD exacerbations. Our study is consistent with previous studies on the utility of LUS in identifying patients with elevated NP in patients with heart failure, that is LUS B‐lines are specific (~90%) but the sensitivity is variable (30–90%) . In this study of patients with COPD exacerbations, we also found that LUS B‐lines have moderate sensitivity for identifying patients with elevated NP.…”
Section: Two‐way Paired Comparisons Between Acute Exacerbation Of Chrsupporting
confidence: 91%
“…The pathognomonic feature on LUS used to diagnose cardiac failure is the identification of sonographic artefacts caused by extravascular lung water, thickening the lobular septa, called ‘B‐lines’ . Studies in cardiac failure patients have shown that LUS B‐lines are specific (90%) and sensitive (33–90%) for elevated NPs . Using LUS to identify cardiac failure is radiation‐free, typically takes 1 to 5 min to complete and has low inter and intra‐observer variability .…”
Section: Two‐way Paired Comparisons Between Acute Exacerbation Of Chrmentioning
confidence: 99%
“…The major finding of our study corroborates and extends previous findings. 2 onstrated by point-of-care LUS display a very high specificity to support the diagnosis of AHF in ED patients with acute dyspnoea (specificity 75-91 %) [7,8]. In contrast to previous examinations, diagnostic sensitivity in our trial (40 %) is moderate as compared to previous reports (70 -92 %) [7,8].…”
contrasting
confidence: 51%
“…2 onstrated by point-of-care LUS display a very high specificity to support the diagnosis of AHF in ED patients with acute dyspnoea (specificity 75-91 %) [7,8]. In contrast to previous examinations, diagnostic sensitivity in our trial (40 %) is moderate as compared to previous reports (70 -92 %) [7,8]. It is tempting to speculate that this may be due to the method of final adjudication of AHF diagnosis in respective trials: Final adjudicated diagnosis of AHF in our trial was done by 2 experienced physicians (cardiologist, emergency physician) using all available patient data for adjudication [1,10], while other reports used scores including descriptive methods of pulmonary congestions and/or cardiac decompensation for final diagnosis questioning accuracy of final adjudicated diagnosis [6,8].…”
mentioning
confidence: 99%
“…This increases the plasma concentration of β-EP to 5 to 6 times. [ 10 12 ] β-EP is the main junction with opioid receptors and is involved in the pathological processes of many diseases, such as pain, breathing, circulation, digestion, and the hypothalamus-pituitary-target gland function, which play an important role. Its action mechanism mainly includes: the inhibition of catecholamine (CA) and prostaglandin (PG) on the regulation of cardiovascular function, inhibiting myocardial contraction force, the expansion of the capillaries, combined with capillary permeability of the blood, and bleeding that causes blood pressure to drop and shock; allow β-EP release to inhibit the respiratory center, reduce medulla, aorta, aortic sinus chemoreceptor sensitivity to hypoxia and hypercapnia, respiratory frequency and lower tidal volume, lessen ventilatory response caused by CO 2 , oxygen and CO 2 retention, leading to more β-EP released into the bloodstream, which is a vicious cycle, and increase in central inhibition; the role in brainstem reticular structure upward excited system and nonspecific thalamus cortex system, participate in the occurrence and development of brain dysfunction, and according to research, opioid receptors in the process of sensory afferent gate have an effect, which is caused by changes associated with EP.…”
Section: Discussionmentioning
confidence: 99%